Transcendent God, Rational World A Maturidi Theology - Harvey, Ramon (Edinburgh University Press, 2021)
Ramon Harvey revisits the Muslim theologian Abū Manṣūr al-Māturīdī (d. 333/944) from Samarqand and puts his system, and that of the Māturīdī school, into lively dialogue with modern thought.Combining rigorous study of Arabic Māturīdī texts with insights from Husserl's phenomenology and analytic theology, Harvey explores themes from epistemology and metaphysics to the nature of God and specific divine attributes (omniscience and wisdom, creative action, divine speech and the Qur'an). His systematic treatment of these topics shows that a contemporary Islamic philosophical theology, or kalām jadīd, can be true to the past, yet dynamic in the present, and can provide original and constructive answers to perennial theological questions.